2023
DOI: 10.1021/acsami.3c00446
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bovine Milk Exosome Using Electrophoretic Oscillation Assisted Tangential Flow Filtration with Antifouling of Micro-ultrafiltration Membrane Filters

Abstract: Tangent flow-driven ultrafiltration (TF-UF) is an efficient isolation process of milk exosomes without morphological deformation. However, the TF-UF approach with micro-ultrafiltration SiN x membrane filters suffers from the clogging and fouling of microultrafiltration membrane filter pores with large bioparticles. Thus, it is limited in the long term, continuous isolation of large quantities of exosomes. In this work, we introduced electrophoretic oscillation (EPO) in the TF-UF approach to remove pore cloggin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…81,82 EVs were isolated from whey by ultracentrifugation 43,80,82,83 after EV concentration using tangential flow filtration, as reported previously. 84,85 Initially, the size distribution of EVs was evaluated by nanoparticle tracking analysis (NTA) and dynamic light scattering (DLS) measurement. As a result, the mean and hydrodynamic diameters of EVs were 109 and 102 nm, respectively (Figure 2a, solid line; Table 1), and their size was favorable to achieving tumor accumulation via the EPR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…81,82 EVs were isolated from whey by ultracentrifugation 43,80,82,83 after EV concentration using tangential flow filtration, as reported previously. 84,85 Initially, the size distribution of EVs was evaluated by nanoparticle tracking analysis (NTA) and dynamic light scattering (DLS) measurement. As a result, the mean and hydrodynamic diameters of EVs were 109 and 102 nm, respectively (Figure 2a, solid line; Table 1), and their size was favorable to achieving tumor accumulation via the EPR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…99 In addition, a study showed that combined electrophoretic oscillation-assisted tangent flow (EPOTF) filtration could isolate milk exosomes with high concentration, high purity and intact morphology. 100 Another method was designed by integrating a zwitterionic tandem membrane system, and one of the filters was modified with sulfobetaine methacrylate (SBMA) hydrogel to isolate exosomes. 101…”
Section: Other Methodsmentioning
confidence: 99%
“…To date, there have been various separation, purification, and enrichment methods for collecting EVs, such as ultracentrifugation (Roerig et al., 2022 ), ultrafiltration (Ko et al., 2023 ), size exclusion chromatography (Lisi et al., 2023 ), polyethylene glycol precipitation (Jalaludin et al., 2023 ) and so on. Ultracentrifugation separates EVs based on the density, size, and shape of solutes.…”
Section: Mass Production Of Extracellular Vesiclesmentioning
confidence: 99%